The Role of Organisational Culture in Shaping Academic Supervision Practices in Madrasah Ibtidaiyah - Rizkarima; Mulyawan Safwandy Nugraha (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
Academic supervision in madrasahs is not implemented solely through formal procedures but may develop in response to the organisational culture embedded within the institution. This study aims to analyse how organisational culture shapes academic supervision practices and to explain how these practices develop into teachers’ professional learning in a Madrasah Ibtidaiyah. The study employed a qualitative approach with a case study design at MI Asih Putera, Cimahi City. Data were collected through semi-structured interviews with the principal, vice principal, and senior teacher, a questionnaire administered to 14 teachers as supporting triangulation data, observations, and document analysis. Data were analysed through data condensation, data display, conclusion drawing and verification, and thematic analysis using source and method triangulation. The findings demonstrate that organisational culture provides the foundation for adapting academic supervision practices, which subsequently develop into a mechanism for teachers’ professional learning. The study proposes a conceptual model linking organisational culture, adapted academic supervision, and teachers’ professional learning within the madrasah context.